Mentoring for Innovation: Key Factors Affecting Participant Satisfaction in the Process of Collaborative Knowledge Construction in Teacher Training - Dorner, Helga; Kárpáti, Andrea (Online Learning, 2010)
This paper presents data about the successful use of the Mentored Innovation Model for professional development for a group of Hungarian teachers (n=23, n=20 in two iterations), which was employed in the CALIBRATE project in order to enhance their ICT skills and pedagogical competences needed for participation in a multicultural, multilingual educational innovation process. This model relied on the three basic constituents of an online community of inquiry: cognitive, social and teaching presence. Satisfaction regarding the model was explored through the observation of perceived (subjective) values provided by the participating respondents in order to identify the role of the virtual learning environments employed, activities of the facilitator and the participants’ self-perceived social presence in the success of the training process. Mentoring was identified as a key factor of success in the in-service training process.